Let's talk! Clinical research project of therapeutic occupation activities on conversation and social interaction - Dias, Carlos Manuel de Melo (2019)
Schizophrenia is implied as a disease that impairs thinking, perception and interaction and social functioning. Therapeutic Occupation Activities (TOA) promote, prevent, empower, and recover social skills, appropriate verbal and nonverbal behaviors; with the evidence showing the pertinence, effectiveness and benefits of this learning and training. This scientific partnership between ESEnfC, CHUC, Rehabilitation Unit and UCAERe-T, designed in a Single Case Experimental Design, has as main goal to evaluate the effectiveness of the structured TOA program of Conversation and Social Interaction of learning and training communication skills/conversation with Schizophrenia Patients. Expressing the results with the Personal and Social Performance Scale and the Scale for Interpersonal Behaviour, it is expected a relative improvement of the various clinical outcomes, namely: personal and social functioning; social involvement; social interaction skills; personal well-being; interpersonal behavior; mood balance; motivation; self-esteem; and personal autonomy.